Multisite and bidirectional exonic splicing enhancer in CD44 alternative exon v3 - Vela, Elena (Cold Spring Harbor Laboratory Press, 2007)

(untitled)
The human CD44 gene encodes multiple isoforms of a transmembrane protein that differ in their extracellular domains as a result of alternative splicing of its variable exons. Expression of CD44 is tightly regulated according to the type and physiological status of a cell, with expression of high molecular weight isoforms by inclusion of variable exons and low molecular weight isoforms containing few or no variable exons. Human CD44 variable exon 3 (v3) can follow a specific alternative splicing route different from that affecting other variable exons. Here we map and functionally describe the splicing enhancer element within CD44 exon v3 which regulates its inclusion in the final mRNA. The v3 splicing enhancer is a multisite bipartite element consisting of a tandem nonamer, the XX motif, and an heptamer, the Y motif, located centrally in the exon. Each of the three sites of this multisite enhancer partially retains its splicing enhancing capacity independently from each other in CD44 and shows full enhancing function in gene contexts different from CD44. We further demonstrate that these motifs act cooperatively as at least two motifs are needed to maintain exon inclusion. Their action is differential with respect to the splice-site target abutting v3. The first X motif acts on the 3′ splice site, the second X motif acts on both splice sites (as a bidirectional exonic splicing enhancer), and the Y motif acts on the 5′ splice site. We also show that the multisite v3 splicing enhancer is functional irrespective of flanking intron length and spatial organization within v3.